Self-care and Self-Compassion in University Student Athletes - Ally Heasman; Dana Scannell; Eithne Hunt (Baltic Journal of Sport and Health Sciences, 2025)
Background: Student athletes (SA) face unique challenges in balancing academic and athletic demands, frequently impacting well-being. This study aimed to measure levels of self-care and self-compassion in SA in one university in Munster, Ireland and also aimed to investigate the relationship between these and identify some ways that universities could support SA in strengthening self-care and self-compassion behaviours.